As simulações educacionais no ensino de Física : aplicando uma UEPS sobre a primeira Lei da Termodinâmica utilizando a abordagem POE - Souza, Fernando de Jesus (2023)
Thermodynamics integrates the study of the laws that govern the relationships between heat, work and other forms of energy, about such concepts high school students present alternative conceptions that do not always match the scientific explanation of the terms, which makes learning difficult and makes the most challenging Physics Teaching. Thus, the use of more collaborative teaching techniques that allow the active participation of students is a way to raise learning levels. In view of this, this work aimed to investigate the conceptual evolution of the first law of thermodynamics of students in the 2nd year of high school based on educational simulations with the POE method (predict, observe, explain) in a Potentially Significant Teaching Unit (UEPS). The study was carried out in a state school in Poço Verde/SE, using a qualitative approach and a case study. The results showed that the application of the UEPS, with the use and handling of the simulations and the POE method, increased the class's engagement and involved them in the entire learning process, motivating them to carry out all the steps in the search for the confrontation of hypotheses. We can therefore conclude that UEPS with the use of simulations with the POE method on the first law of thermodynamics, developed and applied during this research, can be a possibility for teaching physics and increasing the significant learning of thermodynamics concepts.